Digital populism and fabricated authenticity in Jair Bolsonaro’s Instagram campaign - Maia, Lídia Raquel Herculano (2022)
This research investigates the affirmation of authenticity through the sharing of everyday life on the Instagram profile of the presidential candidate Jair Bolsonaro and some of his supporters, in the 2018 elections. To this end, the empirical analysis is systematized around three categories (identity, transparency and engagement) of political authenticity, proposed in the theoretical model of Gilpin, Palazzolo and Brody (2010). Starting from exploratory research with a qualitative approach, we used the abductive method to analyze materials published by this politician and some of his supporters on Instagram. Our results show that Jair Bolsonaro managed to create a supposedly authentic image through the construction of the identity of a “simple man”. That characteristic demonstrates a suppose transparency by weaving a zone of direct contact with the electorate; making it clear that as a candidate, he needed the engagement of the fans to win the dispute and defeat the “enemies of the people”, in a populist rhetoric that harmonizes with the logic of the social media